State of the science in reconciling top‐down and bottom‐up approaches for terrestrial CO2 budget. (12th December 2019) - Kondo, Masayuki; Patra, Prabir K.; Sitch, Stephen; Friedlingstein, Pierre; Poulter, Benjamin; Chevallier, Frederic; Ciais, Philippe; Canadell, Josep G.; Bastos, Ana; Lauerwald, Ronny; Calle, Leonardo; Ichii, Kazuhito; et al.
Abstract: Robust estimates of CO2 budget, CO2 exchanged between the atmosphere and terrestrial biosphere, are necessary to better understand the role of the terrestrial biosphere in mitigating anthropogenic CO2 emissions. Over the past decade, this field of research has advanced through understanding of the differences and similarities of two fundamentally different approaches: "top‐down" atmospheric inversions and "bottom‐up" biosphere models. Since the first studies were undertaken, these approaches have shown an increasing level of agreement, but disagreements in some regions still persist, in part because they do not estimate the same quantity of atmosphere–biosphere CO2 exchange. Here, we conducted a thorough comparison of CO2 budgets at multiple scales and from multiple methods to assess the current state of the science in estimating CO2 budgets. Our set of atmospheric inversions and biosphere models, which were adjusted for a consistent flux definition, showed a high level of agreement for global and hemispheric CO2 budgets in the 2000s. Regionally, improved agreement in CO2 budgets was notable for North America and Southeast Asia. However, large gaps between the two methods remained in East Asia and South America. In other regions, Europe, boreal Asia, Africa, South Asia, and Oceania, it was difficult to determine whether those regions act as a net sink or source because of the large spread in estimates from atmospheric inversions. These results highlight two research directions to improve the robustness of CO2 budgets: (a) to increase representation of processes in biosphere models that could contribute to fill the budget gaps, such as forest regrowth and forest degradation; and (b) to reduce sink–source compensation between regions (dipoles) in atmospheric inversion so that their estimates become more comparable. Advancements on both research areas will increase the level of agreement between the top‐down and bottom‐up approaches and yield more robust knowledge of regional CO2 budgets. Abstract : Recent atmospheric inversions and biosphere models adjusted for a consistent net CO2 flux definition progressed toward closer reconciliation of global and hemispheric CO2 budgets in the 2000s. Yet at the regional scale, the degree of reconciliation remains region‐specific. We highlight two key points for the future reconciliation of CO2 budgets: (a) incomplete processes in biosphere models, such as the age effects on forest regrowth, and degradation, have a potential role in filling the budget gaps between the methods; and (b) uncertainties in sink–source compensation between regions (dipoles) need to be reduced for having more comparable budget estimates within atmospheric inversions.